The Leadership Role of The Principal in Increasing Admission of New Students - Muhammad Mulya Al-Amien; Achadi Budi Santosa (Institut Agama Islam Negeri (IAIN) Curup, 2021)
This study aims to reveal the role of school principals in increasing new student admissions. The method used in this research is qualitative. Collecting data through documentation, observation, and interviews. Respondents include school principals, vice principals, and heads of expertise programs. The results showed that the principal's role in increasing new student admissions was to optimize his function as an educator, which is to always provide guidance, as a manager who always encourages teachers and education personnel, especially those who are included in the committee to carry out their duties in accordance with the plans and rules that have been outlined. in its main duties and functions. As a supervisor, the school principal always monitors, provides input, direction, and motivation to all members of the new student admissions program committee. The principal is also always a role model in discipline, and is always active in establishing relationships with junior high schools in his area. The results of this study are certainly quite inspiring, because the implications can encourage the spirit of school principals in improving the performance of the new student admissions committee in each school.